Utilization Study of Halimeda macroloba Extract as Natural Preservative Materials in Cakalang Fish Meat (Katsuwonus pelamis) - Dewinta, Astrid Fauzia; Hutajulu, Valencia; Siregar, Rizky Febriansyah; Yusni, Eri (AQUACOASTMARINE: Journal of Aquatic and Fisheries Sciences, 2023)
The purpose of this study was to characterize the secondary metabolites in Halimeda macroloba by means of phytochemical screening tests, and to determine the use of the best concentration of Halimeda macroloba extract to maintain the freshness quality of skipjack tuna physically, chemically and microbiologically. The results of the phytochemical screening test showed that the green macroalgae Halimeda macroloba contains alkaloids, steroids and triterpenoids, saponins, flavanoids, tannins and glucosides. The organoleptic physical test results for the best parameters of meat appearance, aroma and texture were in the A5 concentration treatment (600 ppm) with a value of 8.43, then the chemical test results found that the best protein content and TVB values ​​were found in treatment A5 (600 ppm) with a value of 22.9% and in the A4 treatment (400 ppm) with a value of 9.24 mgN/100g. Meanwhile, the microbiological test results showed that the best TPC value was found in treatment A5 (600 ppm) with a value of 0.5×105 col/gram.